2020
DOI: 10.1097/md.0000000000019425
|View full text |Cite
|
Sign up to set email alerts
|

Study on urinary metabolomics of premenstrual dysphoric disorder patients with liver-qi depression syndrome treated with Xiaoyaosan

Abstract: Introduction: Premenstrual dysphoric disorder (PMDD) is a serious form of premenstrual syndrome with mental symptoms as its main manifestation, which seriously affects women's health and daily life. Some basic research and clinical studies have shown that the Chinese herbal medicine of Xiaoyaosan can relieve the symptoms of mental disorders with few side effects. The aim of this study is to evaluate the clinical efficacy of Xiaoyaosan for treating PMDD with liver-qi depression syndrome. In addition, metabonomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The infarct-limiting effects of baicalin in myocardial I/R damage are associated with the inhibition of mitochondrial damage-mediated apoptosis (Wang et al, 2013). Baicalin also rescued myocardial I/R-induced damage, decreased myocardial apoptosis and inflammation by activating PI3K/AKT, but inhibiting NF-κB and JAK/STAT pathway (Luan et al, 2019;Xu et al, 2020). Ferroptosis is an iron-dependent form of necrotic cell death which occurs in myocardial I/R injury (Doll et al, 2019;Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The infarct-limiting effects of baicalin in myocardial I/R damage are associated with the inhibition of mitochondrial damage-mediated apoptosis (Wang et al, 2013). Baicalin also rescued myocardial I/R-induced damage, decreased myocardial apoptosis and inflammation by activating PI3K/AKT, but inhibiting NF-κB and JAK/STAT pathway (Luan et al, 2019;Xu et al, 2020). Ferroptosis is an iron-dependent form of necrotic cell death which occurs in myocardial I/R injury (Doll et al, 2019;Ma et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…If GAD symptoms can be reversed in the early stage of the disease, it can not only greatly alleviate the great mental pain experienced by patients with GAD, but also avoid the occurrence of depression to a certain extent. DZXYS has been widely used in the clinical treatment of GAD and has a definite curative effect on the disease, but it has not received extensive international attention because of its unclear treatment mechanism ( Xu et al, 2020 ). Through this study, we found that the deep-seated molecular mechanism of DZXYS promotes neuronal regeneration in the hippocampus to treat GAD by downregulating the Notch signaling pathway, which not only opens up new ideas for the development of more effective anti-anxiety drugs in the future, but also lays a foundation for further exploration of the effective components in the prescription.…”
Section: Discussionmentioning
confidence: 99%
“…It originated from Xue Ji’s Internal Medicine Abstract during the Ming Dynasty. It was modified by the “Xiaoyao Powder.” The entire prescription consisted of 10 g danpi, 10 g gardenia, 15 g bupleurum, 10 g Poria cocos, 15 g fried Atractylodes macrocephala, 10 g Angelica sinensis, 10 g white peony, 10 g licorice, 3 g mint, and 9 g ginger, which is widely used in clinical and experimental research on anxiety and depression disorder ( Xu et al, 2020 ). Our team’s previous research found extensive neuronal apoptosis and neuronal regeneration disorders in the hippocampus of GAD rats.…”
Section: Introductionmentioning
confidence: 99%
“…TCM experts generally considered that depression is closely related to Qi and blood blockage and liver unreel distributing [ 25 , 26 ]. All kinds of negative emotional stimulation, such as mental panic, physical and mental exhaustion, and failure to achieve one's goals, can cause dysfunction of viscera, Qi, and blood and lead to depression.…”
Section: Yin Deficiency and Internal Heat Of Depressionmentioning
confidence: 99%